Crystal structures of five halido gold complexes involving piperidine or pyrrolidine as ligands or (protonated) as cations - Cindy Döring; Peter G. Jones (Acta Crystallographica Section E: Crystallographic Communications, 2023)
In bromido(pyrrolidine-κN)gold(I) bis(pyrrolidine-κN)gold(I) bromide, [AuBr(pyr)]·[Au(pyr)2]Br (pyr = pyrrolidine, C4H9N), 2, alternating [AuBr(pyr)] molecules and [Au(pyr)2]+ cations are connected by aurophilic contacts to form infinite chains of residues parallel to the b axis. The chains are cross-linked by three N—H...Br− hydrogen bonds and an Au...Br contact to form a layer structure parallel to the ab plane. Trichlorido(piperidine-κN)gold(III), [AuCl3(pip)] (pip = piperidine, C5H11N), 3, consists of molecules with the expected square-planar coordination at the gold atom, which are connected by an N—H...Cl hydrogen bond and an Au...Cl contact to form a layer structure parallel to the ac plane. The structures of bis(piperidinium) tetrachloridoaurate(III) chloride, (pipH)2[AuCl4]Cl, 4, and bis(pyrrolidinium) tetrabromidoaurate(III) bromide, (pyrH)2[AuBr4]Br, 6, are closely related but not isotypic. Compound 6 crystallizes in space group Ibam; the Au and two Br atoms of the anion lie in the mirror plane x, y, 0, whereas the bromide ions occupy special positions 0, 0.5, 0 and 0, 0.5, 0.25, with site symmetry 2/m. The NH2 group forms a hydrogen bond to one bromide ion, and also a three-centre hydrogen bond to the other bromide atom and to a metal-bonded Br atom. The packing involves chains of hydrogen-bonded pyrrolidinium and bromide ions parallel to the c axis, combined with a layer structure of [AuBr4]− and bromide anions, parallel to the ab plane and involving Au...Br and Br...Br contacts. Compound 4, however, crystallizes pseudosymmetrically in space group Iba2; two chlorine atoms of the anion lie on the twofold axis 0.5, 0.5, z, and there are two independent cations. The packing is closely similar to that of 6, but there are no N—H...Cl hydrogen bonds to metal-bonded chlorines. The contact distances Au...Cl are appreciably longer than their Au...Br counterparts in 6, whereas the Cl...Cl contact is much shorter than Br...Br in 6. Tribromido(piperidine-κN)gold(III) crystallizes as its dichloromethane solvate, [AuBr3(pip)]·CH2Cl2, 7. It too displays a square-planar coordination at the gold atom. The packing involves hydrogen bonds N—H...Br, stacking of neighbouring AuBr3 units by Au...Br contacts, and a short Br...Br contact; these combine to form a layer structure parallel to the ac plane.